WOUND HEALING PROPERTIES OF VRANASHODHANAHARA TAIL AND DOORVADI TAIL AS AN EXPERIMENTAL AND COMPARATIVE STUDY ON ALBINO RATS - K. Jain, Vinod; Kumawat, Naresh K.; Shankar Rao, K.; Zafer, Z.Y. Khan (International Journal of Ayurveda and Pharma Research, 2015)
In Ayurveda, for oil preparations Tila oil is used as a base (good for wound healing), on external application attracts oil soluble toxic substances and can be washed out easily with lukewarm water. Study done on healthy albino rats of either sex were selected randomly and were divided into six groups (control group (P), group for Vranashodhanahara tail (V) and group for Doorvadi tail (D) which subdivided into two groups), each containing four albino rats for evaluation and effect of prepared samples on wound healing. For the purpose of study two types of wounds were produced experimentally, excised or open wound (Morton and Mallone) and incised or sutured wound (Hunts et. al.). The assessment was made by studying the regeneration tissue by different parameters viz. wound contraction and period of epithelialisation and tensile strength. The gross appearance was noted at the interval of 3 days i.e., 3rd, 6th, 9th and 12th day of applying wounds. The results show that excised wound contracted earlier in treated groups while in the trial groups complete closure was achieved around 14th day, where as in the control-P group, it was achieved around 17th day and incised wound indicating that trial V group provided better result than control P.